Laws of Language and Legal Language: A Study of Legal Language in Some Indonesian Regulations - Shidarta Shidarta (Humaniora, 2017)
Legal language must follow the laws of language (grammar) that widely known and commonly used by the public, including groups of the scientist. Legal language on the other hand also recognizes specific terminologies. These terminologies were introduced by jurists or by legislative power holders. Accordingly, legal language became the product of legal doctrines or political decisions. The problems arose when a number of compositions and legal terms turned out to be elusive, convoluted, and ambiguous due to the pattern of writing that was once done and because of certain considerations. This article proposed reviewing the factors that result in problems. The author presented a solution to observe using hermeneutic methods of law and legal reasoning. The author argued that the text of the law was not neutral since it was trapped not only by the laws of language but also by the perspective of the interpreters as they believed such a perspective was based on the guidance of legal science. By using legal hermeneutics can be checked the depth of the meaning of the law; while over the legal reasoning can be seen its rationale according to legal science.